A Matter of Life and Death: Alternative Stable States in Trees, From Xylem to Ecosystems - Hammond, William M. (Frontiers in Forests and Global Change, 2020)
Global forests are experiencing widespread climate-induced mortality. Predicting this phenomenon has proven difficult, despite recent advances in understanding physiological mechanisms of mortality in individual trees along with environmental drivers of mortality at broad scales. With heat and drought as primary climatic drivers, and convergence on hydraulic failure as the primary physiological mechanism, new models are needed to improve our predictions of Earth’s forests under future climate conditions. While much of ecology focuses on equilibrium states, transitions from one stable state to another are often described with alternative stable state theory (ASST), where systems can settle to more than one stable condition. Recent studies have identified threshold responses of hydraulic failure during tree mortality, indicating that alternative stable states may be present. Here, we demonstrate that the xylem of trees has characteristics indicative of alternative stable states. Through empirical evidence, we identify a catastrophic shift during hydraulic failure which prevents trees from returning to pre-droughted physiological states after environmental stressors (e.g., drought, heat) are relieved. Thus, the legacy of climate-induced hydraulic failure likely contributes to reduced resilience of forests under future climate. I discuss the implications and future directions for including ASST in models of tree mortality.